2023
DOI: 10.1007/s00330-023-09461-y
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in BreastScreen Norway: a retrospective analysis of a cancer-enriched sample including 1254 breast cancer cases

Abstract: Objectives To compare results of selected performance measures in mammographic screening for an artificial intelligence (AI) system versus independent double reading by radiologists. Methods In this retrospective study, we analyzed data from 949 screen-detected breast cancers, 305 interval cancers, and 13,646 negative examinations performed in BreastScreen Norway during the period from 2010 to 2018. An AI system scored the examinations from 1 to 10, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several prior studies explored AI performance in relation to breast density, noting a relative decline of standalone AI performance as breast density increases [ 40 – 42 ]. However, another study reported consistent sensitivity for an AI system with increased breast density, while radiologists’ sensitivity decreased [ 43 ]. In our study, performance metrics of the standalone AI were superior in women with non-dense breasts compared to dense breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies explored AI performance in relation to breast density, noting a relative decline of standalone AI performance as breast density increases [ 40 – 42 ]. However, another study reported consistent sensitivity for an AI system with increased breast density, while radiologists’ sensitivity decreased [ 43 ]. In our study, performance metrics of the standalone AI were superior in women with non-dense breasts compared to dense breasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the classification system has faced challenges due to the significant interobserver variability among radiologists, leading to inconsistencies and uncertainties in assessments [5][6][7]. Recent advancements in artificial intelligence (AI) and deep learning (DL) have demonstrated the potential to improve diagnostic accuracy in medical imaging [8][9][10]. This study investigates the efficacy of a deep learning-enhanced computer-aided diagnosis (CAD) system in evaluating breast tissue density according to the BI-RADS density classification.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in artificial intelligence (AI) and deep learning (DL) have demonstrated the potential to improve diagnostic accuracy in medical imaging [ 8 , 9 , 10 ]. This study investigates the efficacy of a deep learning-enhanced computer-aided diagnosis (CAD) system in evaluating breast tissue density according to the BI-RADS density classification.…”
Section: Introductionmentioning
confidence: 99%
“…Cancers 2023, 15, 3069 2 of 12 Studies have reported that AI performance is comparable to or might even outperform humans in the interpretation of screening studies [4][5][6][7][8]. In these studies, performance is often assessed in terms of general outcome metrics such as cancer detection rate and recall rate [9], but information on the prognostic features of screen-detected breast cancers is frequently not provided.…”
Section: Introductionmentioning
confidence: 99%